Current state and prospects of the development of the world’s hydropower industry under modern conditions ("Journal "U". Economy. Management. Finance.", 2023)
The article presents the analysis of the state of hydropower by region. The main leading countries in the hydropower industry have been identified and the world leadership of Russia in the last decades has been confirmed. The features of the development of hydroelectric power plants in remote areas of the world are noted, as well as the main problems for the countries are highlighted with the ways to solve them. The assumption that the level of hydropower development depends on the economic state of the country is substantiated. An assessment of the further development of the industry is given.
Keywords: hydropower; renewable energy sources; electricity export; hydropower capacity; investment; regional profile